EFEK KOPIGMENTASI DARI KATEKOL DAN TANIN TERHADAP STABILITAS ANTOSIANIN BEKATUL BERAS KETAN HITAM (Oryza sativa glutinosa) SELAMA PENYIMPANAN [Copigmentation Effect of Catechol and Tannin on Stability of Glutinous Black Rice Bran (Oryza sativa glutinosa) Anthocyanins During Storage] - Dian Wulandari; Tirza Hanum; Azhari Rangga (Jurnal Teknologi & Industri Hasil Pertanian, 2018)
Copigmentation has been suggested as an effective method to improve color and stability of anthocyanins and storage time.  Catechol and tannin can be used as a copigment to improve stabilize color of anthocyanins. This study aims to examine the effect of molar ratio of copigment to anthocyanin and storage time which stabilize anthocyanin.This study was arranged in factorial Randomized Complete Block Design (RCBD) with three replications. First factor were molar ratio 0:1, 50:1, 100:1; and second factor were time of storage 0, 10, 20, 30, 40 days at room temperature (28oC ± 2 oC).  Color and stability of anthocyanins were evaluated by thrugh determination of bathochromic and hyperchromic, anthocyanins concentration, retention, and kinetic parameters.  Variables were analyzed by Tuckey test, Bartlet test, and Polynomial Orthogonal test.The results showed that anthocyanin content of glutinous black rice bran extract was 426 mg/100g. Copigmentation with catechol resulted in bluish color (hypsochromic), while tannin resulted in reddish color (bathochromic).  The best molar ratio of catechol copigment was 50: 1 showed by decreasing of anthocyanin concentration of 0.35mM/day or 39.29mg/100g/day, color retention 12.78%/hour, and half-life time 8.66 hours. The best molar ratio of tannins copigment was 100: 1 showed by decreasing of anthocyanin concentration of 0.07mM/day or 7.86mg/100g/day, color retention was 2.39%/day, and half-life time of 19.80 hours.